Ammonia and pH inhibition in anaerobic treatment of wastewaters, part II: Model development - ÇALLI, BARIŞ (TAYLOR & FRANCIS INC, 2004)
A new model to account for the influences of pH and ammonia on methane production in the anaerobic treatment of wastewaters is presented. The model is developed and evaluated by using two different sets of experimental data obtained using seeds from two different full-scale industrial anaerobic reactors. One of the seeds was obtained from an expanded granular sludge-blanket (EGSB) reactor treating a corn processing waste. The other seed was obtained from an upflow anaerobic sludge-blanket reactor (UASB) treating waste from a potato chips production plant. Model development is based on the data collected at four different pH values (6.8, 7.4, 7.8, 8.4) and with six different TAN (Total Ammonia Nitrogen) values (262mg/L (control), 1000, 1500, 2000, 2500, 3000). The proposed model has a considerably more convenient form compared to other models that have been used in the literature for similar purposes. For example, the model facilitates the calculation of quantities such as the optimal pH as a function of TAN concentration, or the TAN concentration leading to 50% inhibition (TAN(50)) as a function of pH. High levels of correlations were achieved by the application of the proposed model to the experimental data obtained during our studies.
Keywords: ammonia; anaerobic treatment; inhibition; methanogen; modeling; METHANOGENIC SLUDGE; DIGESTION; TOXICITY